1998
DOI: 10.1086/514604
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Cytomegalovirus and Herpesviruses 6, 7, and 8 in Saliva of Human Immunodeficiency Virus Type 1–Infected Patients and Healthy Controls

Abstract: We used the polymerase chain reaction to study the presence of DNA from cytomegalovirus (CMV) and human herpesvirus (HHV)-6, HHV-7, and HHV-8 in saliva from 44 human immunodeficiency virus (HIV) type 1 -infected patients at different stages of disease and in 15 healthy HIVseronegative controls. CMV DNA, HHV-6 DNA, and HHV-7 DNA were found in all groups, but HHV-8 DNA was found only in symptomatic HIV-1-infected patients (5 [17%] of 29). One of the patients with HHV-8 DNA in saliva had oral Kaposi's sarcoma at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
2
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 3 publications
10
56
2
5
Order By: Relevance
“…These data are consistent with other studies that showed high CMV and EBV salivary shedding among more immunosuppressed patients in comparison with HIV-seronegative individuals 4,7,10 . Even in patients submitted to HAART, EBV and CMV shedding appears to persist at a higher frequency compared with HIV-uninfected controls 8,12 . This finding is in agreement with other studies in Brazil that also showed a high prevalence of CMV and EBV in HIV-seropositive patients 10;35 .…”
Section: Ethicalmentioning
confidence: 93%
See 2 more Smart Citations
“…These data are consistent with other studies that showed high CMV and EBV salivary shedding among more immunosuppressed patients in comparison with HIV-seronegative individuals 4,7,10 . Even in patients submitted to HAART, EBV and CMV shedding appears to persist at a higher frequency compared with HIV-uninfected controls 8,12 . This finding is in agreement with other studies in Brazil that also showed a high prevalence of CMV and EBV in HIV-seropositive patients 10;35 .…”
Section: Ethicalmentioning
confidence: 93%
“…The transmission of these viruses occurs by contact with infected secretions, especially saliva [3][4][5][6] . The majority of HHV infected individuals show no clinical symptoms, but can shed HHVs asymptomatically in saliva 4,7,8 .…”
Section: Article/artigomentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, HHV-8 DNA was found in unstimulated whole saliva from 25 of 76 HIV-infected individuals without oral KS 23 , and another study showed HHV-8 in the saliva of individuals having no detectable viral sequences in their peripheral blood mononuclear cells 24 . In addition, HHV-8 DNA was detected in the saliva of 5 of 29 (17%) symptomatic HIV-infected patients (only 1 had oral KS at the time of sampling), but in none of 15 healthy controls 25 or in any of 39 HIV-negative patients 26 .…”
Section: Epidemiology Of Hhv-8 -Aspects Of Transmissionmentioning
confidence: 99%
“…9 Shedding of EBV in the saliva of healthy carriers occurs frequently, 17 whereas oral shedding of CMV, apart from congenital or primary infection, is seen mostly in immunocompromised patients. 18 To our knowledge, no studies have been performed that prospectively sampled HSCT patients, regardless of the presence of oral ulcers, and quantitatively analyzed the presence of HSV-1, EBV and CMV DNA. Also, no data are available on the differential role of herpesvirus excretion on ulcerations at oral sites that may be affected by chemoradiation-induced oral mucositis (nonkeratinized mucosa) and at sites atypical for chemoradiationinduced mucositis (keratinized mucosa).…”
Section: Introductionmentioning
confidence: 99%